Pembuktian Aktivitas Antibakteri Ekstrak Daun Ketul (Bidens pilosa L) Terhadap Pertumbuhan Escherechia Coli Secara Invitro - Lukas Seran; Rikardus Herak (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Traditionally, people of every ethnicity often use traditional medicines made from plants to treat diseases that attack humans. Likewise, in Oelnasi Village, Central Kupang District, Kupang Regency, people used to drink boiled ketul leaves (Bidens pilosa L) to cure diarrheal diseases. The certainty of the medicinal efficacy of boiled ketul leaves taken from Timor has never been scientifically proven. Therefore, research to prove it needs to be done. This study aims to prove the activity of extract of ketul leaf (Bidens pilosa L) from Timor as an antibacterial against the growth of Escherichia coli In vitro. This type of research is a laboratory experiment using Posttest Only Control Group Design which consists of four treatments which were repeated three times. The data were analyzed using one-way ANOVA and continued with the smallest significant difference test (BNT) with a significance level of 1%. The results showed that ketul leaf extract (Bidens pilosa, L) from Timor was proven to have antibacterial activity against the growth of Escherichia coli in vitro. Based on the results of the 1% Key BNT follow-up test that the 20% concentration was significantly different from the 40%, 60% and 80% concentrations; the concentration of 40% was significantly different from the concentration of 20%, 40% and 80%; concentration of 60% was significantly different with concentrations of 20%, 40% and 80%; concentration of 80% was significantly different with concentrations of 20%, 40%, and 60%.